Conceptualizing the Role and Influence of Student–Teacher Relationships on Childrenʼs Social and Cognitive Development - Davies, Heather A. (Educational Psychologist, 2003)
The purpose of this article is to add to our current understanding of the social contexts of education by synthesizing research on the nature and influence of relationships between students and their teachers. I was guided by 3 questions. First, how have we conceptualized students' relationships with teachers? Second, how have our approaches to studying relationships shaped our understanding of the phenomenon? Third, looking across these different approaches to studying student-teacher relationships, what do we know about the nature and influence of student-teacher relationships developmentally? Specifically, I review in 3 broad themes the multiple conceptions, or approaches, to the study of student-teacher relationships. These include student-teacher relationships from attachment perspectives, from motivation perspectives, and from sociocultural perspectives. I view each approach a posing a critical question needing to be addressed conceptually, methodologically, and developmentally. Looking across approaches, findings reveal 1 limitation of our current understanding of student-teacher relationships is that is most of our knowledge about relationships for a particular population of students (e.g., preschool, elementary school, middle school, or high school) is embedded within knowledge about a particular approach (e.g., attachment, motivation, or sociocultural) as well as within specific methods of studying relationships. Implications for future research and theory development are discussed.
Keywords: compétence; contexte pédagogique; motivation